Rancang Bangun Sistem Pengajuan Skripsi Prodi Teknik Informatika Universitas Pamulang Berbasis Web - Dias Mahendra; Nur’aini Nur’aini; Alvino Octaviano (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2022)
Currently, the world of education has entered the digital era. The use of information systems as a technology support can be used to speed up the process, space, and time is started to developed. Minithesis is a scientific essay and becomes an academic assignment from a university to be one of the requirements for graduating students as undergraduates. There are many obstacles in submitting the minithesis manually, especially in the current pandemic situation. Submission of a minithesis at the Informatics Engineering Study Program at Pamulang University still uses a manual system, so there is a need for an easy-to-use application to streamline the academic processes in it. Research The design of the minithesis submission system in the Informatics Engineering Study Program, Pamulang University aims to analyze, design an information system for minithesis submission, and its traceability system. There are several mehod used in this study, namely the method of software development, data collection, system analysis and data design, as well as implementation and testing using black box testing. The results showed that the minithesis submission application was successfully made in accordance with the research design. The parties involved in this process can use the features made in accordance with the system design, and the results of system testing using black box testing have also been successfully carried out. The addition of features is needed, so that the appearance of the application can be more attractive and can also be developed based on android/ios systems.